Faktor-Faktor Yang Berhubungan dengan Pemanfaatan Pelayanan Antenatal Care (ANC) di Wilayah Kerja Puskesmas Simpang Tiga Kabupaten Aceh Besar Tahun 2022 - Misliati Misliati; Maidar Maidar; Wardiati Wardiati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Antenatal care coverage in Indonesia In 2021, K1 was recorded at 98,0% and the percentage of K4 coverage was 88,8% (Kemenkes RI, 2022). Antenatal care coverage at Simpang Tiga K1 Health Center was 83,5% and K4 antenatal care coverage was 53,4%. While the target (RPJMN) in 2021 is 85%, this shows the low number of antenatal care visits at the Simpang Tiga Health Center. The purpose of this study was to determine the factors related to the use of antenatal care services in the work area of the Simpang Tiga Health Center, Aceh Besar District 2022. This research is a descriptive analytic with a cross sectional design. The study was conducted at the Simpang Tiga Public Health Center, Aceh Besar District in 2022. The population in this study were mothers who gave birth, sampling using a total sampling technique of 41 people. The instrument in this study used a questionnaire. Data analysis using chi- square test at alpha = 0,05). The resulth of this study found that as many as 85,37% of respondents used complete antenatal care services. The results of statistical tests showed that there was a relationship between education level (p-value: 0,009), dan knowledge (p-value: 0,0015) with the use of antenatal care services. Meanwhile, age (p-value: 0,148) and occupation (p-value: 0,567) are not relate to the use of antenatal care services. It is expected that pregnant women can use antenatal care services at least 4 times, for families to support mothers in regular antenatal care checks. And it is hoped that health workers can educate pregnant women about antenatal care and can provide antental care services with predetermined standards.